2018
DOI: 10.1021/acsami.8b11157
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide-Anchored Manganese Hexacyanoferrate with Low Interstitial H2O for Superior Sodium-Ion Batteries

Abstract: Low-cost manganese hexacyanoferrate (NMHCF) possesses many favorable advantages including high theoretical capacity, ease of preparation, and robust open channels that enable faster Na diffusion kinetics. However, high lattice water and low electronic conductivity are the main bottlenecks to their pragmatic realization. Here, we present a strategy by anchoring NMHCF on reduced graphene oxide (RGO) to alleviate these problems, featuring a specific discharge capacity of 161/121 mA h g at a current density of 20/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 42 publications
0
47
0
Order By: Relevance
“…Wang et al reported the addition of RGO during precipitation of NaMnHCF. [ 133 ] Surprisingly, not only the morphology and stoichiometry of the precipitates are changed, but also the crystal water in the NaMnHCF is removed, the latter is evidenced by the structure change from monoclinic (Na 1.67 Fe[Mn(CN) 6 ] 0.9 ·1.47H 2 O) to rhombohedral (Na 1.89 Fe[Mn(CN) 6 ] 0.98 ·0.16H 2 O) and the single‐plateau electrochemical profile. However, the water removal and structure change are not observed for Na 1.83 Mn 0.83 Ni 0.12 Fe(CN) 6 /RGO prepared likewise.…”
Section: Dehydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al reported the addition of RGO during precipitation of NaMnHCF. [ 133 ] Surprisingly, not only the morphology and stoichiometry of the precipitates are changed, but also the crystal water in the NaMnHCF is removed, the latter is evidenced by the structure change from monoclinic (Na 1.67 Fe[Mn(CN) 6 ] 0.9 ·1.47H 2 O) to rhombohedral (Na 1.89 Fe[Mn(CN) 6 ] 0.98 ·0.16H 2 O) and the single‐plateau electrochemical profile. However, the water removal and structure change are not observed for Na 1.83 Mn 0.83 Ni 0.12 Fe(CN) 6 /RGO prepared likewise.…”
Section: Dehydrationmentioning
confidence: 99%
“…With superior conductivity and large surface area, graphene and reduced graphene oxide (RGO) have been intensively used to complex with HCFs. [ 108,133,134,148,149,152–155 ] Han's group fabricated a free‐standing NaFeHCF/RGO (16 wt%) electrode by a series of protocols including liquid N 2 quenching, free‐drying and hydrazine reduction (Figure 15d–g). [ 149 ] The liquid N 2 quenching can promote self‐scrolling of the GO nanosheets into 1D nanorolls in which the NaFeHCF particles are firmly encapsulated.…”
Section: Compositing and Surface Modificationmentioning
confidence: 99%
“…Indeed, as a result of the porous nature of PBAs, these materials act as sponge‐like materials towards water molecules. However, the hydration degree affects the electrochemical performance sharply as substantial differences are seen in the electrochemical signature of fully or partially (presence of interstitial water) dehydrated materials . However, the effect of adsorbed water is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the existence of Na‐rich rhombohedral phase can be further verified by the splitting peaks at around 24° and 39° in the patterns of the sample discharging to 2.0 V. Through the patterns of all samples, the peak splitting and merging can be clearly observed due to the cubic‐rhombohedral phase transition, as schematically shown in Figure c. [ 39,40 ] Moreover, as shown in Figure 5c,d, FeHCFe nanoframes show less expansion of the crystal structure during charging up to 4.2 V, which can be confirmed by the shift angle of the (200) peak. 2θ angle of the peak of FeHCFe nanoframes electrode was increased by 0.2° upon further charging up to 4.2 V compared with the first discharging to 2.0 V, which is smaller than that of the FeHCFe nanocubes electrode (0.24°).…”
Section: Resultsmentioning
confidence: 80%